A European Analysis of Changes in Gender Specific Wage Inequality Using Decomposition Methods - Behr, Andreas (Journal of Income Distribution®, 2007)
We analyze wage growth and changes in wage inequality in eleven Europeancountries between 1994 and 2001. The data base used throughout is the User DataBase (UDB) of the European Community Household Panel (ECHP). The decompositionanalysis is carried out independently for both genders. Following Juhn, Murphyand Brooks (1991; 1993) we split the current wage into components to isolate theforces underlying the wage change. While the decomposition method is in the spiritof the well known Oaxaca decomposition (1973), in the approach of Juhn, Murphy,and Pierce the residual of Mincerian-earnings equations is decomposed further intorelative rank position and the effect of the residual distribution.We find wage inequality to be greater among men for most northern countriesof the EU, while in southern countries, wage inequality is greater among women.Between 1994 and 2001, wage inequality was found to have moved in the same directionfor men and women in all countries. Inequality increased in five countries,most pronouncedly in the Netherlands; inequality decreased in six countries, mostmarkedly in Ireland. Decomposition of the changes in inequality into quality, price,and unobserved effects revealed that the quality effect explained only a minor partof the total change. Changes in prices for individual characteristics are found to bethe most important source of inequality changes for women, and about as important aschanges in residual effects are for men. Altogether, the heterogeneous development ofwages across the European Union does not hint at a common trend toward the risinginequality that has been observed in the United States for decades.